1999
DOI: 10.1056/nejm199907083410202
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive Lipid-Lowering Therapy Compared with Angioplasty in Stable Coronary Artery Disease

Abstract: In low-risk patients with stable coronary artery disease, aggressive lipid-lowering therapy is at least as effective as angioplasty and usual care in reducing the incidence of ischemic events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
318
0
31

Year Published

2001
2001
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 816 publications
(354 citation statements)
references
References 11 publications
5
318
0
31
Order By: Relevance
“…Statin-treated persons showed decreased macrophages, T-cells, and apoptotic cells in atherosclerotic plaques, with a linear relationship between the degree of LDL lowering and the reduction in risk of CVD events that was shown recently in a report in which fluvastatin decreased death and myocardial infarction by 58%, with particular benefit in persons with diabetes (39). In another study, atorvastatin 80 mg daily without angioplasty decreased LDL cholesterol to 77 mg/dl, with 13% 18-month risk of ischemic events, in comparison to an ischemic event rate of 21% among persons undergoing angioplasty with mean LDL cholesterol 119 mg/dl (40). Selwyn noted, however, that too often physicians do not administer statins "with any vigor at all, despite evidence that those persons given such treatment have improved outcome.…”
Section: Studies In Manmentioning
confidence: 85%
“…Statin-treated persons showed decreased macrophages, T-cells, and apoptotic cells in atherosclerotic plaques, with a linear relationship between the degree of LDL lowering and the reduction in risk of CVD events that was shown recently in a report in which fluvastatin decreased death and myocardial infarction by 58%, with particular benefit in persons with diabetes (39). In another study, atorvastatin 80 mg daily without angioplasty decreased LDL cholesterol to 77 mg/dl, with 13% 18-month risk of ischemic events, in comparison to an ischemic event rate of 21% among persons undergoing angioplasty with mean LDL cholesterol 119 mg/dl (40). Selwyn noted, however, that too often physicians do not administer statins "with any vigor at all, despite evidence that those persons given such treatment have improved outcome.…”
Section: Studies In Manmentioning
confidence: 85%
“…Recent studies have suggested that in low-risk patients with stable coronary artery disease, aggressive lipid lowering therapy might be at least as effective as angioplasty in reducing the incidence of ischemic events, emphasizing the importance of treating risk factors. [23][24][25] We have no comparative group of patients with stable angina pectoris who were not referred for catheterization. Thus, we cannot exclude the possibility that patients not undergoing invasive investigations might receive a more appropriate medical therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to past management, when PCI and medical therapy had been considered as alternate, competing strategies for symptomatic CAD (18,19), lipid-lowering therapy is now seen as providing early, complementary benefit in combination with coronary revascularization. However, in a recent survey, only 26.5% of 5052 patients undergoing PCI were receiving statin treatment at the time of the procedure (10).…”
Section: Methods: Patients Undergoing a First Pci Between August 2000mentioning
confidence: 99%